2021
DOI: 10.7759/cureus.16379
|View full text |Cite
|
Sign up to set email alerts
|

Social Data: An Underutilized Metric for Determining Participation in COVID-19 Vaccinations

Abstract: Many measures have been taken since late 2019 to combat the coronavirus disease (COVID-19) pandemic. National, state, and local governments employed precautions, including mask mandates, stay-at-home orders, and social distancing policies, to alleviate the burden on healthcare workers and slow the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus until an efficacious vaccine was made widely available. By early spring of 2021, three effective and well-tolerated SARS-CoV-2 vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Though surgical intervention was largely preferred for many years, minimally invasive treatments have grown in popularity due to their favorable outcomes, fast recovery times, low overhead, and accessibility [2]. To empirically capture the shift in interest from surgical to minimally invasive gluteal augmentation, a five-year retrospective analysis of Google Trends relative search volume (RSV) was conducted, as many Google Trend studies have demonstrated the relationship between internet search volume and procedural participation [20][21][22][23][24]. Our analysis demonstrates a shifting interest from surgical gluteal augmentation ('butt surgery') to injectable augmentation ('butt filler') (Figure 2).…”
Section: Figure 1: Proposed Biostimulatory Mechanism Of Action Of Cah...mentioning
confidence: 99%
“…Though surgical intervention was largely preferred for many years, minimally invasive treatments have grown in popularity due to their favorable outcomes, fast recovery times, low overhead, and accessibility [2]. To empirically capture the shift in interest from surgical to minimally invasive gluteal augmentation, a five-year retrospective analysis of Google Trends relative search volume (RSV) was conducted, as many Google Trend studies have demonstrated the relationship between internet search volume and procedural participation [20][21][22][23][24]. Our analysis demonstrates a shifting interest from surgical gluteal augmentation ('butt surgery') to injectable augmentation ('butt filler') (Figure 2).…”
Section: Figure 1: Proposed Biostimulatory Mechanism Of Action Of Cah...mentioning
confidence: 99%